Integration and reanalysis of transcriptomics and methylomics data derived from blood and testis tissue of men with 47, XXY Klinefelter syndrome indicates the primary involvement of Sertoli cells in the testicular pathogenesis. Issue 2 (25th May 2020) - Winge, Sofia B.; Soraggi, Samuele; Schierup, Mikkel H.; Rajpert‐De Meyts, Ewa; Almstrup, Kristian
Abstract: Klinefelter syndrome (KS; 47, XXY) is the most common sex chromosomal anomaly and causes a multitude of symptoms. Often the most noticeable symptom is infertility caused by azoospermia with testicular histology showing hyalinization of tubules, germ cells loss, and Leydig cell hyperplasia. The germ cell loss begins early in life leading to partial hyalinization of the testis at puberty, but the mechanistic drivers behind this remain poorly understood. In this systematic review, we summarize the current knowledge on developmental changes in the cellularity of KS gonads supplemented by a comparative analysis of the fetal and adult gonadal transcriptome, and blood transcriptome and methylome of men with KS. We identified a high fraction of upregulated genes that escape X‐chromosome inactivation, thus supporting previous hypotheses that these are the main drivers of the testicular phenotype in KS. Enrichment analysis showed overrepresentation of genes from the X‐ and Y‐chromosome and testicular transcription factors. Furthermore, by re‐evaluation of recent single cell RNA‐sequencing data originating from adult KS testis, we found novel evidence that the Sertoli cell is the most affected cell type. Our results are consistent with disturbed cross‐talk between somatic and germ cells in the KS testis, and with X‐escapee genes acting as mediators.